1948
DOI: 10.1192/bjp.94.395.351
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of British Troops in the Far East

Abstract: The general importance of studying the mental health of British troops in the Far East is obvious enough. It is perhaps less obvious that this importance is unlikely to have diminished with the end of the war; for there are still many troops serving in the Far East, and presumably will be for some time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1950
1950
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The acute reactive psychiatric state, as in war, is not a matter of individual neurosis, latent or otherwise, but of the individual's 'fit' or adaptation to the particular environment. This accords with the 'chink in the armour' theory of breakdown in servicemen of good personality put forward by Tredgold (1948).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The acute reactive psychiatric state, as in war, is not a matter of individual neurosis, latent or otherwise, but of the individual's 'fit' or adaptation to the particular environment. This accords with the 'chink in the armour' theory of breakdown in servicemen of good personality put forward by Tredgold (1948).…”
supporting
confidence: 74%
“…He thought that it might result from excessive work and mental strain, and it was characterized by good recovery with rest. In the second world war good personality breakdown came to receive its full recognition and formulation, and was described in servicemen by Sargant and Slater (1940), Garmany (1944), Weinberg (1946), and Tredgold (1948) and in civilians by Gillespie (1942) and Ling (1944). Finally, Appel and Beebe (1946) showed that almost all men in rifle battalions became psychiatric casualties if they remained in a combat area for more than 200 to 240 aggregate combat days, and that a man reached his effective peak in 90 days.…”
mentioning
confidence: 99%
“…In general, British soldiers passed through a difficult phase in their first 6 months of overseas service-a time which coincided with their getting used to separation from home, to the conditions of the new country, and climatic differences. Thereafter, the soldiers who had not broken down in the first 6 months usually remained well-adjusted for the next 2 years, but after 23 years of overseas service difficulties began to increase for nearly all British soldiers (Tredgold, 1948).…”
Section: (B) Length Of' Overseas or Field Servicementioning
confidence: 99%
“…Indian troops : N i l British troops knew that they were going to be separated from their families for from 3 to 7 years (Tredgold, 1948). In the latter stages of the campaign the system of giving 1 month's home leave to very limited numbers of British troops was introduced.…”
Section: (E) Fear Of' Illnessmentioning
confidence: 99%